2020
DOI: 10.1159/000505313
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Frequently Relapsing Minimal-Change Nephrotic Syndrome with Steroid-Induced Psychiatric Syndrome Treated by Low-Dose, Short-Term Steroid Therapy in Combination with Cyclosporine

Abstract: Adults with minimal-change nephrotic syndrome (MCNS) generally receive oral prednisolone (PSL) at an initial dosage of 1.0 mg/kg/day for a minimum of 4 weeks, with 80% of patients achieving clinical remission. However, relapses are frequent, necessitating repeated treatment with high-dose PSL. Long-term treatment with high-dose steroids increases the risk of steroid toxicities, such as diabetes mellitus, gastric complications, infections, osteoporosis, and steroid-induced psychiatric syndrome (SIPS), which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been reported that CsA can be prescribed in the pediatric population for indications such as “childhood psoriasis, pediatric dermatoses, auto-immune hemolytic anemia (AIHA), and the relapsing nephrotic syndrome”. [ 63 64 ]…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CsA can be prescribed in the pediatric population for indications such as “childhood psoriasis, pediatric dermatoses, auto-immune hemolytic anemia (AIHA), and the relapsing nephrotic syndrome”. [ 63 64 ]…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the widely known side effects of steroids have led to the exploration of new strategies that minimize the dose of corticosteroids utilized for MCD treatment ( 13 ). To date, the most widely employed strategy to minimize the steroid dose at the initial flare is based on the combination of LDS with non-steroidal immunosuppressants such as mycophenolate mofetil ( 14 , 15 ), tacrolimus ( 16 ), cyclophosphamide ( 17 ), cyclosporin ( 18 ), and the recently proposed rituximab ( 19 , 20 ). Despite the recurrent disease profile of this podocythopathy, only a limited number of studies have evaluated steroid minimization strategies for relapse therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of CsA and prednisolone can reduce the initial dosage of prednisolone, hence shortening the time to remission and easily maintaining it. This combination protocol indicated the effectiveness and usefulness and could potentially be a future treatment strategy for frequent-relapse nephrotic syndrome [ 57 ]. The most crucial drawback of CsA ( Table 1 ) could be the high relapse rate after withdrawal of the medication.…”
Section: Treatment Options In MCDmentioning
confidence: 99%